Algicidal Bacteria: A Review of Current Knowledge and Applications to Control Harmful Algal Blooms - Coyne, Kathryn J.; Wang, Yanfei; Johnson, Gretchen (Frontiers in Microbiology, 2022)
Interactions between bacteria and phytoplankton in aqueous ecosystems are both complex and dynamic, with associations that range from mutualism to parasitism. This review focuses on algicidal interactions, in which bacteria are capable of controlling algal growth through physical association or the production of algicidal compounds. While there is some evidence for bacterial control of algal growth in the field, our understanding of these interactions is largely based on laboratory culture experiments. Here, the range of these algicidal interactions is discussed, including specificity of bacterial control, mechanisms for activity, and insights into the chemical and biochemical analysis of these interactions. The development of algicidal bacteria or compounds derived from bacteria for control of harmful algal blooms is reviewed with a focus on environmentally friendly or sustainable methods of application. Potential avenues for future research and further development and application of bacterial algicides for the control of algal blooms are presented.